Uremic Toxins: An Alarming Danger Concerning the Cardiovascular System - Falconi, Carlos Alexandre; Junho, Carolina Victoria da Cruz; Fogaça-Ruiz, Fernanda; Vernier, Imara Caridad Stable; da Cunha, Regiane Stafim; Stinghen, Andréa Emilia Marques; Carneiro-Ramos, Marcela Sorelli (Frontiers in Physiology, 2021)
The kidneys and heart share functions with the common goal of maintaining homeostasis. When kidney injury occurs, many compounds, the so-called “uremic retention solutes” or “uremic toxins”, accumulate in the circulation targeting other tissues. The accumulation of uremic toxins such as p-cresyl sulfate, indoxyl sulfate and inorganic phosphate leads to a loss of a substantial number of body functions. Although the concept of uremic toxins is dated to the 1960s, the molecular mechanisms capable of leading to renal and cardiovascular injuries are not yet known. Besides, the greatest toxic effects appear to be induced by compounds that are difficult to remove by dialysis. Considering the close relationship between renal and cardiovascular functions, an understanding of the mechanisms involved in the production, clearance and overall impact of uremic toxins is extremely relevant for the understanding of pathologies of the cardiovascular system. Thus, the present study has as main focus to present an extensive review on the impact of uremic toxins in the cardiovascular system, bringing the state of the art on the subject as well as clinical implications related to patient’s therapy affected by chronic kidney disease, which represents high mortality of patients with cardiac comorbidities.